2016
DOI: 10.3892/etm.2016.3411
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of elevated serum A-FABP and free fatty acid in neonates with hypoxic ischemic brain damage

Abstract: The main function of adipocyte fatty acid-binding protein (A-FABP) is to regulate fatty acid metabolism as its molecular chaperone. The clinical significance of A-FABP in hypoxic-ischemic brain damage (HIBD) neonates is not yet clear. Free fatty acid (FFA) in cerebral cortex increases along with hypoxia ischemia degree. Thus, we aimed to investigate whether FFA can induce A-FABP expression and elevate the serum A-FABP level in HIBD neonates. In the present study, 42 HIBD neonates were selected including 11 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Indeed, an increase thereof is associated with the pathogenesis of obesity and of obesity-related diseases [151,152]. Moreover, it has been found that there is a positive correlation between SFAs and the severity of hypoxic-damage in the brain, and finally, a direct proportionality emerged between the intake of SFAs and markers of acute myocardial infarct [153,154,155].…”
Section: Saponifiable Fractionmentioning
confidence: 99%
“…Indeed, an increase thereof is associated with the pathogenesis of obesity and of obesity-related diseases [151,152]. Moreover, it has been found that there is a positive correlation between SFAs and the severity of hypoxic-damage in the brain, and finally, a direct proportionality emerged between the intake of SFAs and markers of acute myocardial infarct [153,154,155].…”
Section: Saponifiable Fractionmentioning
confidence: 99%
“…Elevated FABP disrupts the blood-brain barrier and causes cerebral ischemic injury in mice [65]. Higher levels of FABP have been reported in the serum of neonates having a hypoxic injury [66].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated FABP disrupts the blood‐brain barrier and causes cerebral ischemic injury in mice [65]. Higher levels of FABP have been reported in the serum of neonates having a hypoxic injury [66]. According to the Human Developmental Biology Resource (HDBR), the RNA‐seq data of prenatal human brain development shows FABP1 expression in the cerebellum, medulla oblongata, and spinal cord regions of neonatal brain [67].…”
Section: Discussionmentioning
confidence: 99%